Theoretical conceptions for a holistic, transdisciplinary approach to contemporary landscape. - Alba-Dorado, María Isabel (Springer, 2023)
In recent years the concept of landscape has undergone rapid expansion. This expansion, however, has not been accompanied by a parallel development in the definition of theoretical and methodological principles, nor has it achieved sufficient consensus for its application in scientific and/or administrative fields. The range of divergent ideas that currently persist and coexist around the concept of landscape, and which are biased towards disciplinary specificities, have given rise not only to terminological imprecision, but also to a lack of standardisation of study, evaluation, management and planning methodologies. This article aims to provide an overview of the different acceptations that have been developed in relation to the concept of landscape from the second half of the 20th century to the present day, with a view towards contributing to the conceptual and disciplinary plurality that exists regarding landscape as an entity. This study, however, also attempts to transcend this analysis by advancing towards the definition of a conceptual framework on which to redefine the concept of landscape by considering the multiplicity of dimensions that may be attributable to this concept and advocating a holistic, transdisciplinary, open, integrative approach to these dimensions.
Keywords: Paisaje - Evaluación; Landscape; Dimensions; Transdisciplinary systems; Holistic approach